Perancangan 1×6 Linear Array Antena Dipole Pada Frekuensi 38 GHZ Untuk 5G Smartphone - Hikmah Adi Putra; Yusnita Rahayu; Adit Kurniawan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The 5G technology is the next phase of wireless network communication development. Adaptation of Multiple Input Multiple Output (MIMO) techniques into 5G technology is used to produce high data rate communication, low power consumption and bigger network capacity compared to 4G technology. Antenna design that can work on millimeter waves with high gain, better efficency and compact size antenna is needed for 5G mobile devices. This paper proposed the design of MIMO antenna for 5G smartphone application with gain>10 dBi and bandwidth>500 MHz. The proposed antenna is designed by RT Duroid 5880 substrate with the overall size of 44,8x4,4x078 mm3, consisting of 1x6 element linear array antenna. The proposed antenna yields bandwidth of 5,68 GHz at frequencies range 36.05 GHz to 41.74 GHz and 11.4 dBi of gain at 38 GHz frequency.Keyword: Antenna Smartphone, 5G, Beam steerable, MIMO.